2010
DOI: 10.1200/jco.2009.25.4672
|View full text |Cite
|
Sign up to set email alerts
|

End-of-Life Discussions, Goal Attainment, and Distress at the End of Life: Predictors and Outcomes of Receipt of Care Consistent With Preferences

Abstract: A B S T R A C T PurposePhysicians have an ethical obligation to honor patients' values for care, including at the end of life (EOL). We sought to evaluate factors that help patients to receive care consistent with their preferences. MethodsThis was a longitudinal multi-institutional cohort study. We measured baseline preferences for life-extending versus symptom-directed care and actual EOL care received in 325 patients with advanced cancer. We also measured associated sociodemographic, health, and communicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
595
3
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 721 publications
(639 citation statements)
references
References 28 publications
18
595
3
8
Order By: Relevance
“…In addition, for some patients, continuing bevacizumab may provide psychological benefits. Mack et al [18] recently showed that a minority of patients with advanced cancer desired attempts at life-extending therapy, even after recognizing the terminal nature of their disease. Although this subgroup of patients did not succeed in prolonging their lives, the authors note that some patients may nonetheless want assurance that they did "everything possible" to extend life.…”
Section: Beneficence: the Hope Of Benefitmentioning
confidence: 99%
“…In addition, for some patients, continuing bevacizumab may provide psychological benefits. Mack et al [18] recently showed that a minority of patients with advanced cancer desired attempts at life-extending therapy, even after recognizing the terminal nature of their disease. Although this subgroup of patients did not succeed in prolonging their lives, the authors note that some patients may nonetheless want assurance that they did "everything possible" to extend life.…”
Section: Beneficence: the Hope Of Benefitmentioning
confidence: 99%
“…In fact, patients who recognize a poor prognosis are more likely to receive the care they want (whether intensive life-prolonging care or care focused on symptoms) at the end of life. 29 Conversations about prognosis thus support patient autonomy and value-driven decision-making, not just 1 kind of care.…”
Section: Benefits Of Prognosis Communication: What Is the Evidence?mentioning
confidence: 99%
“…Having timely end-of-life discussions (EOLds) with advanced cancer patients is essential; multiple empirical studies demonstrate that EOLds reduce unnecessary aggressive care near death, provide end-of-life (EOL) care consistent with patients' preferences, increase early hospice referrals, and improve patients' quality of life [1][2][3][4][5]. Many physicians, however, do not actually discuss EOL options with advanced cancer patients until they are in the terminal phase of life [6,7].…”
Section: Introductionmentioning
confidence: 99%